The α-Al2 O3 microparticles drive decreasing effects on the sperm quality of rainbow trout - Özgür, ME; Ulu, A; Özcan, İ; Balcıoğlu, S; Noma, SAA; Ateş, B; Köytepe, S (Journal of the Hellenic Veterinary Medical Society, 2024)
This work examined the effects of alpha-alumina microparticles (α-Al2O3-MPs) on the reproductive efficiency of rainbow trout, Oncorhynchus mykiss sperm cells. The α-Al2O3-MPs (~100 nm) were characterized by Fourier Transform Infrared Spectrometer, X-Ray spectrum and Scanning Electron Microscope. After exposure with α-Al2O3-MPs (0.125, 0.25, 0.5, 1.0, and 5.0 g/L 24 h, in vitro) on sperm cells, it was determined to the motility parameters and total glutathione (tGSH) and superoxide dismutase (SOD) as biochemical parameters of sperm cells. The velocities of sperm cells decreased after exposure to a 0.125 g/L dose of α-Al2O3-MPs. However, while the tGSH levels increased in a dose-dependent manner α-Al2O3-MPs, the SOD activities decreased. All these changes were significant (p < 0.05) in 1 g/L dose of α-Al2O3-MPs when compared with the control group.